Стародавні карти України в колекції Томаша Нєводнічанського - Буряк, О.; Сосса, Р. (Історико-географічні дослідження в Україні, 2009)
У статті висвітлено історію формування зібрання старовинних карт відомого польського колекціонера Т. Нєводнічанського. Описано найвідоміші карти України, що експонувалися на виставці «IMAGO UKRAINAE. СТАРОВИННІ
КАРТИ УКРАЇНИ З КОЛЕКЦІЇ Т. НЄВОДНІЧАНСЬКОГО»
на початку 2006 р. в Києві, Харкові, Львові. Розглянуто
хронологію проведення виставок карт з колекції Т. Нєводнічанського у різних країнах. The article deals with the history of Tomash Niewodnichanski’s ancient
maps of Ukraine collection formation. The best-known maps of
Ukraine, which was put on display at IMAGO UKRAINAE. THE ANCIENT
MAPS OF UKRAINE FROM THE COLLECTION OF TOMASH
NIEWODNICHANSKI exhibition that took place at the beginning
of the 2006 in Kyiv, Kharkiv, L’viv are the subject of consideration
of the given article. The chronology of conducting of maps exhibitions
from the collection of Tomash Niewodnichanski that have taken place in
different countries is also reviewed in the article.